Generic Placement of the Former Condaliopsis (Rhamnaceae) species - Islam, Melissa Bauer; Guralnick, Robert P. (Phytotaxa, 2015)
Condaliopsis is a genus of eight thorny shrub species. Previous morphological research shed doubt on the validity of Condaliopsis as a distinct genus in Rhamnaceae. Condaliopsis species were transferred to one of two genera, Ziziphus or Condalia, but some authors continue to recognize Condaliopsis. A recent phylogenetic study did not support Condaliopsis as monophyletic and placement of Condaliopsis species in either Ziziphus or Condalia was not straightforward. To clarify the generic placement of these eight species, we conducted phylogenetic analyses based on two nuclear loci (nrITS and 26S), two chloroplast loci (trnL-F and trnQ-rps16) and morphological characters. We present evidence that five of the Condaliopsis species should remain in Ziziphus, one should remain in Condalia, and two should be transferred from Ziziphus to Condalia. One of these species had an existing binomial within Condalia, Condalia parryi, and one required a new combination, Condalia celata. Condalia celata is a federally listed endangered species with a limited range in Florida.